Necrotizing fasciitis in a patient with COVID-19 - Acosta, Nuvia Novoa (2023)
Introduction: SARS-CoV-2 infection generates a higher risk of complications and mortality in previously ill patients, patients with diabetes mellitus have a weaker immune system and the increase in blood glucose can compromise innate immunity and humoral immunity. Therefore, these patients are more susceptible to soft tissue infections. Objective: To describe the evolution and complications of a patient with type II diabetes mellitus with SARS-CoV-2 infection who presented necrotizing fasciitis on the 15th day of disease evolution. Case presentation: A 52-year-old male patient, white, with type II diabetes mellitus and high blood pressure for which he was treated with slow insulin, metformin, enalapril, and hydrochlorothiazide, was admitted as a positive case of COVID-19, at Fifteenth day of stay began with fever, heat and flushing, swelling beyond the area of erythema and crepitus in both lower limbs, surgical intervention was decided. In the operating room, drainage, debridement, and necrectomy were performed on both lower limbs. Microbiological analysis through culture detected the growth of Pantoea agglomerans . Conclusions: Diabetes mellitus, the use of glucocorticoids, were the risk factors found to cause the state of immunosuppression in the case presented, and the use of biological anti-TNF drugs (Nimotuzumab). It is necessary to be insistent on prevention measures: maximum asepsis in the handling of intravenous access, and judicious use of antibiotics.